2017
DOI: 10.1177/1477878517695903
|View full text |Cite
|
Sign up to set email alerts
|

Educating through exemplars: Alternative paths to virtue

Abstract: This paper confronts Zagzebski's exemplarism with the intertwined debates over the conditions of exemplarity and the unity-disunity of the virtues, to show the advantages of a pluralistic exemplar-based approach to moral education (PEBAME). PEBAME is based on a prima facie disunitarist perspective in moral theory, which amounts to admitting both exemplarity in all respects and single-virtue exemplarity. First, we account for the advantages of PEBAME, and we show how two figures in recent Italian history (Giorg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 26 publications
0
28
0
Order By: Relevance
“…In fact, authors have argued that 'close-by' exemplars (in terms of one's everyday experience) are more likely to trigger admiration and the desire to emulate than more 'distant' saints who 'might look too far away from our ordinary experience and hence appear to be less imitable' (Croce & Vaccarezza, 2017, p. 13). Croce and Vaccarezza (2017) argue that heroes, who display one or two virtues to an exceptional degree, are more 'imitable' than saints, who are flawless without qualification (see also, Zagzebski, 2017, chapter 3).…”
Section: Creating More Relatable Storiesmentioning
confidence: 99%
“…In fact, authors have argued that 'close-by' exemplars (in terms of one's everyday experience) are more likely to trigger admiration and the desire to emulate than more 'distant' saints who 'might look too far away from our ordinary experience and hence appear to be less imitable' (Croce & Vaccarezza, 2017, p. 13). Croce and Vaccarezza (2017) argue that heroes, who display one or two virtues to an exceptional degree, are more 'imitable' than saints, who are flawless without qualification (see also, Zagzebski, 2017, chapter 3).…”
Section: Creating More Relatable Storiesmentioning
confidence: 99%
“…17 I have defended this claim at length in Croce and Vaccarezza (2017). 18 Thanks to Duncan Pritchard and two anonymous reviewers for their comments on an earlier version of this paper.…”
Section: Resultsmentioning
confidence: 97%
“…As should be clear from this passage, Zagzebski seems to contemplate the possibility that, at some early stages of moral development, her own categories of moral exemplars might not facilitate the novice's path toward virtue. 4 Several commentators (Croce 2019;Croce and Vaccarezza 2017;Han et al 2017;Szutta 2019) have seriously considered this remark and have suggested that we should broaden the domain of moral exemplars. In particular, Han et al (2017) have shown that novices are less willing to engage with the virtuous deeds of historic exemplars than they are with attainable and relevant exemplars-that is, with figures who provide the novices with the perception that emulating them is within their reach and who exercise the virtues in situations familiar to the novices.…”
Section: Saints Heroes and The Problems With Imitabilitymentioning
confidence: 99%